2018
DOI: 10.1164/rccm.201712-2456oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Dysbiosis, Inflammation, and Injury in Hematopoietic Cell Transplantation

Abstract: In animal models and human subjects, lung dysbiosis is a prominent feature of HCT. Lung dysbiosis is correlated with histologic, immunologic, and physiologic features of post-HCT pulmonary complications. Our findings suggest the lung microbiome may be an unappreciated target for the prevention and treatment of post-HCT pulmonary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 48 publications
(66 reference statements)
3
38
0
Order By: Relevance
“…In addition, many bacterial-, fungi-, and damage-associated molecular patterns can also bind to TLR2 or TLR9 and stimulate NF-κB, leading to the expression of IL-6. BMT conditioning is associated with tissue damage, and we have shown that the lung microbiome community structure and diversity is significantly shifted after MHV-68 infection in BMT mice (28), which we speculate may provide suitable conditions for stimulating cDC2s to become pro-Th17 APCs.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, many bacterial-, fungi-, and damage-associated molecular patterns can also bind to TLR2 or TLR9 and stimulate NF-κB, leading to the expression of IL-6. BMT conditioning is associated with tissue damage, and we have shown that the lung microbiome community structure and diversity is significantly shifted after MHV-68 infection in BMT mice (28), which we speculate may provide suitable conditions for stimulating cDC2s to become pro-Th17 APCs.…”
Section: Discussionmentioning
confidence: 82%
“…HHV infections after SCT can lead to life-threatening diseases such as pneumonitis, encephalitis, or posttransplant lymphoproliferative disease (25). In addition, we and others have recently revealed a strong association between reactivations/infections with herpes or respiratory viruses and the risk of high mortality noninfectious pulmonary complications after SCT, such as idiopathic pneumonia syndrome and bronchiolitis obliterans syndrome (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this family is a member of the Firmicute phylum and we have also shown that loss of Firmicutes in the BALF of human hematopoietic stem cell transplant patients that are experiencing pulmonary complications are associated with increased production of numerous pro-inflammatory cytokines. 68 This is contrary to what was observed in the bleomycin model of fibrosis, 65 demonstrating the heterogeneous complexity in mechanisms driving different models of interstitial lung disease. Thus far, the analyses in the bleomycin and bone marrow transplant models are at a high level looking only at phyla and family differences.…”
Section: Microbial Drivers Of Fibrosismentioning
confidence: 81%
“…We also recently analysed the alterations to the lung and gut microbiome within the murine bone marrow transplantation model of pneumonitis and fibrosis induced by γHV‐68 infection and found that while the process of transplant alone or viral infection alone caused transient dysbiosis, the dual hit was associated with sustained and profound reductions in lung microbial diversity, but there was not a lasting effect on gut microbial diversity . The major family change seen was a loss of Lachnospiraceae in the lungs of mice with pneumonitis and fibrosis.…”
Section: Microbial Drivers Of Fibrosismentioning
confidence: 99%
See 1 more Smart Citation